Continental vs. Global Niche-Based Modelling of Freshwater Species’ Distributions: How Big Are the Differences in the Estimated Climate Change Effects? - Danijela Markovic; Jörg Freyhof; Oskar Kärcher (Water, 2021)
Thermal response curves that depict the probability of occurrence along a thermal gradient are used to derive various species’ thermal properties and abilities to cope with warming. However, different thermal responses can be expected for different portions of a species range. We focus on differences in thermal response curves (TRCs) and thermal niche requirements for four freshwater fishes (Coregonus sardinella, Pungitius pungitius, Rutilus rutilus, Salvelinus alpinus) native to Europe at (1) the global and (2) European continental scale. European ranges captured only a portion of the global thermal range with major differences in the minimum (Tmin), maximum (Tmax) and average temperature (Tav) of the respective distributions. Further investigations of the model-derived preferred temperature (Tpref), warming tolerance (WT = Tmax − Tpref), safety margin (SM = Tpref − Tav) and the future climatic impact showed substantially differing results. All considered thermal properties either were under- or overestimated at the European level. Our results highlight that, although continental analyses have an impressive spatial extent, they might deliver misleading estimates of species thermal niches and future climate change impacts, if they do not cover the full species ranges. Studies and management actions should therefore favor whole global range distribution data for analyzing species responses to environmental gradients.